English a novel - Wang, Gang (Viking, 2009)
During the darkest days of the Cultural Revolution, a twelve-year-old boy named Love Liu wonders what life is like beyond the region of Xinjiang in China's remote northwest. Here, conformity is valued above all else, and suspicion governs every exchange among neighbors, classmates, and even friends. Into this stifling atmosphere comes a tall, clean-shaven teacher from Shanghai, with an elegant gray wool jacket and an English dictionary tucked under his arm. With the dictionary at his disposal, Love Liu throws himself into learning English, and a whole new world opens up for him. But in an atmosphere of accusation and recrimination, one in which the teacher is deemed morally suspect and mere innuendo can cost someone his life, Love Liu's ideals face a test more challenging than any he'll meet in the classroom. A major bestseller in China, with rights sold around the world, English is a transcendent novel about a boy's self-discovery, a country's shame, and the transporting power of language.
"Orig. publ. in Chinese as Ying ge li shi by People's Literature Publishing House, Beijing"--T.p. verso
Keywords: Geschichte; China / History / Cultural Revolution, 1966-1976 / Fiction; China -- History -- Cultural Revolution, 1966-1976 -- Fiction; Fiktionale Darstellung